2014
DOI: 10.1039/c4ob00649f
|View full text |Cite
|
Sign up to set email alerts
|

Copper(ii)-catalyzed C–O coupling of aryl bromides with aliphatic diols: synthesis of ethers, phenols, and benzo-fused cyclic ethers

Abstract: A highly efficient copper-catalyzed C-O cross-coupling reaction between aryl bromides and aliphatic diols has been developed employing a cheaper, more efficient, and easily removable copper(II) catalyst. A broad range of aryl bromides were coupled with aliphatic diols of different lengths using 5 mol% CuCl2 and 3 equivalents of K2CO3 in the absence of any other ligands or solvents to afford the corresponding hydroxyalkyl aryl ethers in good to excellent yields. In this newly developed protocol, aliphatic diols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 47 publications
2
28
2
Order By: Relevance
“…Phenols can be obtained from phenyloxylethanols through an intramolecular nucleophilic substitution [39]. In 2015, the Chae group found difunctionalized ethanes including 2-dimethylaminoethanol and ethylene glycol can function as ligand to work with Cu(OAc) 2 in the presence of KOH, affording phenols from aryl iodides in moderate to excellent yields (Scheme 17) [40].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenols can be obtained from phenyloxylethanols through an intramolecular nucleophilic substitution [39]. In 2015, the Chae group found difunctionalized ethanes including 2-dimethylaminoethanol and ethylene glycol can function as ligand to work with Cu(OAc) 2 in the presence of KOH, affording phenols from aryl iodides in moderate to excellent yields (Scheme 17) [40].…”
Section: Reviewmentioning
confidence: 99%
“…In 2015, on the basis of a successful application of ethylene glycol in a phenol synthesis [39], the Chae group developed a single-step protocol for the direct synthesis of aryl thiols. The protocol employed CuSO 4 ·5H 2 O as the catalyst and KOH or Cs 2 CO 3 as bases, and could convert aryl iodides, and aryl bromides bearing electron-withdrawing groups to the corresponding aryl thiols in good to excellent yields (Scheme 62) [105].…”
Section: Reviewmentioning
confidence: 99%
“…For example, researchers, including Buchwald et al, reported a highly efficient phenanthroline ligand (L2, R 1 , R 2 , R 3 , R 4 ¼ Me, Fig. 19 Therefore, ligand-free Cu-catalyzed O-arylation of aliphatic alcohols remains a challenge. 14- 16 Avoiding the use of different complex and expensive ligands, "ligand-free" copper catalyst systems have been reported recently in the O-arylation of aliphatic alcohols (17-59% yields, Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…We have developed the efficient synthetic methods of phenols and thiophenols through the cross‐coupling of aryl halides and ethylene glycol and 1,2‐ethanedithiol, respectively, under ligand‐free and copper(II)‐catalysis conditions (Figure ). In our proposed reaction pathway, phenols and thiophenols are liberated from the coupled products via the bond fission by intramolecular S N 2.…”
Section: Introductionmentioning
confidence: 99%